HUBUNGAN TINGKAT PENGETAHUAN DAN PERILAKU MERAWAT BAYI DENGAN STATUS KESEHATAN BAYI POST PERAWATAN NICU DI RSUD W. Z. JOHANNES KUPANG - Florentianus Tat (Cintra Bangsa University - Literacy and Publishing Center (CBU-LPC), 2018)
Abstrak This study entitled the relationship between mother's knowledge level and mother's behavior in caring for infant health status of post-nursing baby NICU in Prof. Dr. W. Z. Johannes Hospital in Kupang-NTT, Indonesia, which is motivated by the still high morbidity and mortality of infants and children. Infant mortality can occur at home or in health facilities. Families especially mothers have an important role to prevent infant mortality and death including after treatment at NICU. The objectives of the study looked at the relationship between mother's knowledge level and mother's behavior in caring for infants on post-nurse health status of NICU